2006
DOI: 10.1111/j.1525-1438.2006.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lymph node metastases in vulvar cancer: a review

Abstract: The aim of this study was to review the literature on currently available non- and minimally-invasive diagnostic methods and analysis of primary tumor characteristics for prediction of inguinofemoral lymph node metastases in patients with primary squamous cell carcinoma of the vulva. We used the English language literature in PubMed and reference lists from selected articles. Search terms included vulvar carcinoma, prognosis, lymph node metastases, ultrasound, computer tomography, magnetic resonance imaging, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 80 publications
0
12
0
3
Order By: Relevance
“…Systematic review suggests that computerised tomography (CT), ultrasound, magnetic resonance imaging (MRI), positron emission tomography (PET) and fine-needle biopsy show inconsistent results and are not accurate enough for the routine assessment of groin node status. 61 Sentinel node identification is currently the most promising diagnostic tool for the assessment of lymph node status in vulval carcinoma, [62][63][64][65][66] but its safety is still to be proven. 58 Clearly in pregnancy…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review suggests that computerised tomography (CT), ultrasound, magnetic resonance imaging (MRI), positron emission tomography (PET) and fine-needle biopsy show inconsistent results and are not accurate enough for the routine assessment of groin node status. 61 Sentinel node identification is currently the most promising diagnostic tool for the assessment of lymph node status in vulval carcinoma, [62][63][64][65][66] but its safety is still to be proven. 58 Clearly in pregnancy…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review [5], it was shown that currently available non-invasive diagnostic tests (palpation, ultrasound (with or without FNA cytology), CT, MRI, PET) are not able to exclude inguinofemoral lymph node metastases with a certainty that is high enough to safely omit complete inguinofemoral lymphadenectomy, while the safety of the sentinel node technique is currently being evaluated in phase II studies [6][7][8]. Studies on different histopathogical parameters of the primary vulvar tumor showed a very low (< 1%) risk for inguinofemoral metastases in tumors with a depth of invasion less than 1 mm [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable overtreatment of patients with non-metastatic tumours has been discussed,1012 and with concern to the postoperative sequela and mutilation associated with radical surgery, new tumour markers that could serve as prognostic indicators would be of considerable value to guide treatment decisions. The purpose of this review is to provide a brief summary of some of the molecular pathological markers studied in vulvar squamous cell carcinoma (VSCC) and address their impact as prognostic markers.…”
mentioning
confidence: 99%